Młodzież i młodzi dorośli wobec kryzysu indywidualnego – potrzeba wsparcia społecznego w rozwoju psychicznej niezależności (i dojrzałej tożsamości) - Suchodolska, Jolanta (Kultura-Społeczeństwo-Edukacja, 2016)
The study refers to the problem of the presence of the crisis in psychosocial development of young people – adolescents and young adults. Both the youth and young adults go through numerous, naturally present in human development, moments of increased tension resulting from the appetite for independence and self-sufficiency. This seems to be a common feature for both groups; both adolescents and young adults experience the burden due to overlapping obligations and commitments made to oneself and to the world and which comes from the specific social roles they assume as well as the development – related tasks they perform. The challenges are taken up to find self-fulfillment in numerous new roles, to achieve ambitions of everyday life as well as the future ones. Not surprisingly, in this period a man is believed to be, on the one hand, exposed to the experience of crisis (relating to the search for oneself and one’s own place in life, in social relationships and professional life) and, on the other hand, a young adult most intensely makes its network of social support for further years. In the study, the author refers to the research in which young adults confirm the presence of the crises in their lives. They identify and name these crisis situations and formulate their expectations of the sources and forms of support in the crisis.